2000
DOI: 10.1097/00006565-200008000-00001
|View full text |Cite
|
Sign up to set email alerts
|

A short stay or 23-hour ward in a general and academic children’s hospital: Are they effective?

Abstract: This data demonstrates the robust nature of the short stay ward. At these two very different institutions we have shown improved bed efficient and patient care in a cost-effective way. We have also reported on greater parental satisfaction and early return of the child with their family to the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 20 publications
3
48
2
1
Order By: Relevance
“…The overall rate of successful discharge (85%) for observation patients measured in this investigation falls within suggested guidelines 2 but is less than rates described in previous reports from pediatric OUs in North America, 15,16 Australia, 17 and Singapore. 18 This may be attributable, in part, to the use of less conservative admission criteria in the study OU, allowing the admission of patients who are more ill.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The overall rate of successful discharge (85%) for observation patients measured in this investigation falls within suggested guidelines 2 but is less than rates described in previous reports from pediatric OUs in North America, 15,16 Australia, 17 and Singapore. 18 This may be attributable, in part, to the use of less conservative admission criteria in the study OU, allowing the admission of patients who are more ill.…”
Section: Discussionsupporting
confidence: 45%
“…18 This may be attributable, in part, to the use of less conservative admission criteria in the study OU, allowing the admission of patients who are more ill. Indirect support for this exists, because the number of observation patients who were admitted to the study OU (580 per 10 000 ED visits) was greater than that reported at similar facilities (545/10 000 in Australia 17 and 400/10 000 in Hartford, CT 16 ). The median age and LOS data for our study population are comparable to previously published reports on pediatric OUs.…”
Section: Discussionmentioning
confidence: 87%
“…The spectrum of the cases which presented to the OU in our study (diarrhoea, bronchiolitis, seizures, thallasemia, poisoning/ animal bites, and pneumonia) was similar to those in the previous published literature [1,2,8,9]. The frequency of the unexpected hospitalisations in our study was 9%.…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of the unexpected hospitalisations in our study was 9%. The frequency of the unexpected hospitalisations was 4% to 22% in the previous published studies [6,8,9].…”
Section: Discussionmentioning
confidence: 76%
“…Such practice has been justified by the need for more beds, and decreases in hospital costs (1)(2)(3)(4)(5)(6) , by technological advances in the health area, and risks inherent to hospital admissions (3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%